2001
DOI: 10.1002/jmv.1051
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus genotypes and HBsAg subtypes in refugees and injection drug users in the United States determined by LiPA and monoclonal EIA

Abstract: Hepatitis B virus (HBV) genotyping and hepatitis B surface antigen (HBsAg) subtyping were carried out on sera from 196 HBsAg-positive patients, including 151 refugees entering the United States and 45 injection drug users in Seattle. HBsAg subtyping was performed by enzyme immunoassay (EIA) using a panel of monoclonal antibodies and the HBV genotype was determined by polymerase chain reaction (PCR) followed by detection of amplified HBV DNA by a reverse-phase hybridization line probe assay (LiPA) using genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
3
28
2
Order By: Relevance
“…This is the first study to sub-classify genotype B into subgenotype Ba or Bj in Vietnamese and showed that nearly all cases (99.2%) of genotype B were sub-classified into genotype Ba. Our results corresponded to those of previous studies of native Vietnamese and Vietnamese immigrants from other countries (17,19,(25)(26)(27)(28)(29)(30)(31), but were inconsistent with the report that genotype A was very common in Vietnamese (33). It was reported that genotype C in East Asia was more strongly associated with severe liver disease and risk of HCC than genotype B (12)(13)(14)(15)20,24,35,37,48,49).…”
Section: -------------------------------------------------contrasting
confidence: 82%
See 1 more Smart Citation
“…This is the first study to sub-classify genotype B into subgenotype Ba or Bj in Vietnamese and showed that nearly all cases (99.2%) of genotype B were sub-classified into genotype Ba. Our results corresponded to those of previous studies of native Vietnamese and Vietnamese immigrants from other countries (17,19,(25)(26)(27)(28)(29)(30)(31), but were inconsistent with the report that genotype A was very common in Vietnamese (33). It was reported that genotype C in East Asia was more strongly associated with severe liver disease and risk of HCC than genotype B (12)(13)(14)(15)20,24,35,37,48,49).…”
Section: -------------------------------------------------contrasting
confidence: 82%
“…In contrast to the findings of the above studies in Vietnamese, a study by Song et al reported that genotype A was very commonly observed in HBV-infected Vietnamese patients (98.7%), that the pre-core mutation (G1896A) was not found, and dual core promoter mutations (A1762T/G1764A) were very rare in HCC patients (8%) and were not found in LC patients, CH patients or asymptomatic carriers (ASC) (33). The results reported by Song et al were very surprising, since the results of many other studies in East Asia and some in Vietnam, with only the exception of studies in the Philippines, showed that genotypes B and C were the major HBV genotypes in this region and mutations in the core promoter and pre-core regions were frequently found (8)(9)(10)(12)(13)(14)(15)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, Panessa et al (2009) previously identified a significant association between genotype D and injecting drug use. Moreover, the predominance of genotype D observed in IDUs in this study was consistent with findings reported elsewhere (Lindh et al 2000, Swenson et al 2001, Garfein et al 2004, Alam et al 2007, Alzahrani et al 2009). However, additional studies will be needed to confirm these associations.…”
supporting
confidence: 93%
“…van Steenbergen et al [2002] performed a molecular epidemiological study of acute hepatitis B in Amsterdam, and found that HBV from majority of drug users were genotype D with subtype ayw3. Swenson et al [2001] studied the HBV genotypes and HBsAg subtypes in refugees and injection drug users in the United States, and found that 7 of 15 refugees from former Soviet Union and 17 of 32 drug users were infected with HBV/D with subtype ayw3. Further, they described that HBsAg subtype of HBV/D strains from the majority of the drug users showed regular ayw3 of which HBsAg had Thr 118 and Met 125, whereas that of the seven refugees from Soviet Union showed variant ayw3 of which HBsAg had Val 118 or Ala 118 and Thr 125.…”
Section: Discussionmentioning
confidence: 99%